Global coherence, healing meditations using HeartMath applications during COVID-19 lockdown - Edwards, Stephen D. (HTS teologiese studies, 2020)
International lockdown and social distancing as a response to COVID-19 indicate planetary interconnectedness. This South African case study compared global coherence, healing meditations using HeartMath Global Coherence and Inner Balance electronic applications (apps) before and during a 3-week lockdown period. Methodology integrated quantitative and qualitative components. Findings revealed significant meditation coherence and achievement increases and significant correlational cluster patterns between meditation data and global coherence increases, magnetometer readings. Local and global healing phenomena, dynamics, mechanisms and implications are discussed.Contribution: This article represents research within a paradigm in which the intersection of philosophy, religious studies, social sciences, humanities and natural sciences generate an interdisciplinary, multidisciplinary and transdisciplinary contested discourse.